Pemberian Rehabilitasi Untuk Pecandu Narkotika Golongan I Jenis Metafetamina Dengan Jumlah Narkotika Yang Relatif Sedikit - Wibi Aryandaru Jatmiko; Aryo Fadlian (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to understand and analyze, through the application of the legal position of Class I narcotics, types of methamphetamines and the importance of rehabilitation for suspects who use narcotics. In the court's decision, the detention ruled. The research method used by the researcher in this study is a normative research that uses a legal approach. The conclusion of this study is that amphetamines or methamphetamines classified as psychotropic Group I have undergone changes, previously in Law No. 5 of 1997 on Narcotics, as in Article 153 letter (b) of Law No. 35 of 2009 on specified narcotics. Since the Amendment to the Law of the Republic of Indonesia No. 5 of 1997 on Psychotropic Drugs has been repealed and declared invalid, narcotics where Group I and Group II psychotropic drugs are indicated have been transferred to Narcotics Category I and rehabilitation is urgently needed. To receive rehabilitation that: under Article 54 of the Republic of Indonesia Law No. 35 of 2009 on Narcotics. Article 103 sees criminal rehabilitation as more effective because the Narcotics Act was specifically enacted and includes a two-track system that is mandatory and not optional. particularly. According to Article 103(2) of the Law of the Republic of Indonesia No. 35 of 2009 on Narcotics, rehabilitation is criminally equivalent to imprisonment..